Chloroflexi Dominate the Deep-Sea Golf Ball Sponges Craniella zetlandica and Craniella infrequens Throughout Different Life Stages - Busch, Kathrin; Wurz, Erik; Rapp, Hans Tore; Bayer, Kristina; Franke, Andre; Hentschel, Ute (Frontiers in Marine Science, 2020)
Deep-sea sponge grounds are underexplored ecosystems that provide numerous goods and services to the functioning of the deep-sea. This study assessed the prokaryotic diversity in embryos, juveniles and adults of Craniella zetlandica and Craniella infrequens, common and abundant representatives of deep-sea sponge grounds in the North Atlantic. Our results reveal that symbiont transmission in Craniella sponges likely occurs vertically, as highly similar microbial consortia have been identified in adults, embryos, and juvenile stages. Moreover, transmission electron microscopy revealed high abundances of sponge-associated microorganisms, among which Chloroflexi (SAR 202) were identified as common representatives by amplicon sequencing and fluorescent in-situ hybridization (FISH). Equal diversity metrices, a similar overall prokaryotic community composition and a distinct dominance of the phylum Chloroflexi within all life stages are the key findings of our analyses. Information such as presented here provide understanding on the recruitment of deep-sea sponge holobionts which is needed to develop integrated management tools of such vulnerable marine ecosystems.